Accidental Injury 2014
DOI: 10.1007/978-1-4939-1732-7_22
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Biomechanics

Abstract: During the human postnatal developmental process, extensive tissue and morphological changes occur. Many take place in the first few years of life but substantial development for several body regions continues well into young adulthood. Along with overall change in size, these material and structural changes influence the biomechanical response of child such that they respond differently to traumatic load than an adult. Understanding the unique biomechanical response of the child is challenging, as compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 167 publications
(183 reference statements)
0
2
0
Order By: Relevance
“…No previous study was found that compared passenger kinematics between AEB and MEB among passenger occupants from different age groups, including child passengers. Children also exhibit different neuromuscular control strategies than adults, irrespective of body size (Dotan et al 2012;Arbogast and Maltese 2015).…”
Section: Introductionmentioning
confidence: 99%
“…No previous study was found that compared passenger kinematics between AEB and MEB among passenger occupants from different age groups, including child passengers. Children also exhibit different neuromuscular control strategies than adults, irrespective of body size (Dotan et al 2012;Arbogast and Maltese 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Injury risk curves for military and automotive crashworthiness evaluations and for advancing occupant safety are developed using data from post mortem human subject (PMHS) experiments (Arbogast and Maltese, 2015;Petitjean et al, 2015;Rupp, 2015;Salzar et al, 2015;Wang et al, 2015;Yoganandan et al, 2014;Yoganandan et al, 2016;Yoganandan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%